Differences between Primary and Revision Rhinoplasty: Indications, Techniques, Grafts, and Outcomes. Issue 3 (16th July 2021) - Hacker, Stefan; Pollock, Jonathan; Gubisch, Wolfgang; Haack, Sebastian
Abstract : Background: The nose is at the center of the face and has essential functional and aesthetic properties. Over recent years, rhinoplasty has gained increasing popularity through the influence of "selfies" and social media. As a result, a growing demand for secondary correction has also emerged. Revision rhinoplasty is more complex than primary cases and often requires the use of extranasal grafting material. The authors sought to analyze the indications, techniques, and outcomes after primary and revision rhinoplasty. Methods: A total of 245 patients (153 primary cases and 92 revisions) undergoing surgery at the authors' specialized clinic for facial plastic surgery were included. All patients were treated by an experienced facial plastic surgeon according to the authors' established clinic standards. A retrospective data analysis was performed to evaluate the differences between the groups regarding the indications, intraoperative techniques, and postoperative outcomes. Results: Although more patients sought revision surgery for aesthetic reasons alone than isolated functional issues, almost two-thirds of the revision patients had functional and aesthetic problems in combination. Complex reconstructive techniques, extracorporeal septoplasties, and extranasal grafts were more commonly used in revision cases. The occurrence of another revision during the follow-up period was significantly higher after revision surgery compared to primary rhinoplasty cases (primary rhinoplasty, 10.5 percent; revision surgery, 23.9 percent; p = 0.006). Conclusions: There are differences between primary and revision rhinoplasty that must be appreciated by the treating surgeon. The patient should be informed about the increased complexity of the secondary procedure, the possible need for extranasal grafts, and the increased risk of a further revision. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, IV.